2015
DOI: 10.1080/15592324.2015.1071750
|View full text |Cite
|
Sign up to set email alerts
|

Memristors: Memory elements in potato tubers

Abstract: A memristor is a nonlinear element because its current-voltage characteristic is similar to that of a Lissajous pattern for nonlinear systems. This element was postulated recently and researchers are looking for it in different biosystems. We investigated electrical circuitry of red Irish potato tubers (Solanum tuberosum L.). The goal was to discover if potato tubers might have a new electrical component -a resistor with memory. The analysis was based on a cyclic currentvoltage characteristic where the resisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 28 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Memory and signaling in plants have been well documented, 125,126 though the mechanisms behind them are still being investigated. Volkov et al performed a series of electrical experiments on several plant species: venus flytrap, 127 Mimosa pudica , 123 aloe vera, 128 potato tubers, 129 pumpkin seeds, 130 apples, 131 and impatiens flowers 132 in search of evidence of resitive memory. These plants were selected because some are model organisms for the study of plant electrophysiology and autonomous motion (venus flytrap, M. pudica ), while the others were included to cover a range of different plant and tissue types.…”
Section: Review Of Bioderived Neuromorphic Architecturesmentioning
confidence: 99%
“…Memory and signaling in plants have been well documented, 125,126 though the mechanisms behind them are still being investigated. Volkov et al performed a series of electrical experiments on several plant species: venus flytrap, 127 Mimosa pudica , 123 aloe vera, 128 potato tubers, 129 pumpkin seeds, 130 apples, 131 and impatiens flowers 132 in search of evidence of resitive memory. These plants were selected because some are model organisms for the study of plant electrophysiology and autonomous motion (venus flytrap, M. pudica ), while the others were included to cover a range of different plant and tissue types.…”
Section: Review Of Bioderived Neuromorphic Architecturesmentioning
confidence: 99%
“…Similar properties were found earlier in the Venus flytrap, Mimosa pudica and Aloe vera. [11][12][13][14][15][16] It was explained by an obvious fact that the biological membranes with ion channels had capacitance connected in parallel to transmembrane organized ion channels. Such type of memristing devices with a capacitance is called a generic memristor.…”
Section: Pinched Hysteresis Loop Should Shrink To a Single-valuedmentioning
confidence: 99%
“…9 Johnsen et al found that the sweat ducts in the skin are memristors. 10 We have found memristors in the electrical circuitry of the Venus flytrap, 11,12 potato tubers, 13 apple fruits, Aloe vera 14 and Mimosa pudica. 15 Pharmaceutical analysis showed that the tetraethylammonium chloride (TEACl) blocker of K C channels inhibits memristance of plants.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation